AN UPDATE OF THE HERPETOFAUNA FROM KIM BANG SPECIES AND HABITAT CONSERVATION AREA, HA NAM PROVINCE NORTH VIETNAM - Thi Yen, Do; Thi Thu Ha, Tran; Thi Ngoc Diep, Tran; Trung Dung, Le (Journal of Forestry Science and Technology, 2023)
The topography of the Kim Bang Species and Habitat Conservation Area in Ha Nam province includes limestone ranges, interbedded with sandstone hills, schist and narrow valleys. This report is the result of a further investigation into amphibians and reptiles from Kim Bang Species and Habitat Conservation Area in Ha Nam province. The objective of this report is to present the results of the 10-day surveys in the area to record additional species composition, distribution characteristics and identification of rare species. This paper also identifies threats to the area and provides recommendations for future conservation of the area. During the survey, 22 species were recorded, in which 47 specimens belonging to 11 families, three orders including 17 reptiles belonging to seven families, two orders and seven species of amphibians belonging to four families, one order. 16 species were reported for the first time of Ha Nam herpetofauna. Additionally, the data of morphological characters of afore mentioned species are also provided. In terms of conservation concern, two species are listed in the IUCN Red List (2022) and seven species is listed in the Vietnam Red Data Book (2007). Kim Bang biodiversity is heavily threatened by habitat degradation and over harvesting associated with wildlife trade. To preserve the unique biodiversity of Kim Bang limestone mountain, we must not only continue with research, in particular the ecological characteristics of recorded species.